Multi-rate tracking controller analysis and design for target tracking systems - Hong, Hua-jie; Li, Zhi-qiang; Fan, Shi-xun; Zhou, Qing-kun; Fan, Da-peng (Journal of Central South University, 2013)
As the sampling rates of the inner loop and the outer loop of the target tracking control system are different, a typical digital multi-rate control system was formed. If the traditional single-rate design method was applied, the low sampling rate loop will seriously impact the dynamical characteristic of the system. After analyzing and calculating the impact law of the low sampling rate loop to the bandwidth and the stability of the tracking system, a kind of multi-rate control system design method was introduced. Corresponding to the different sampling rates of the inner loop and the outer loop, the multi-rate control strategy was constituted by a high sampling rate sub-controller and a low sampling rate sub-controller. The two sub-controllers were designed separately and connected by means of the sampling rate converter. The low sampling rate controller determined the response rapidity of the system, while the high sampling rate controller applied additionally effective control outputs to the system during a sampling interval of the low sampling rate controller. With the introduced high and low sampling rates sub-controllers, the tracking control system can achieve the same performance as a single-rate controller with high sampling rate, yet it works under a much lower sampling rate. The simulation and experimental results show the effectiveness of the introduced multi-rate control design method. It reduces the settling time by 5 times and the over shoot by 4 times compared with the PID control.